State of play of women's participation in urban governance in greater Lomé, Togo - Dounwourgue, Nagbandjoa; Oyedele, Peter; Gbekley, Efui Holaly; Aholou, Coffi; Kola, Edinam (Edelweiss Applied Science and Technology, 2024)
Women's participation in urban governance depends on a certain number of factors, including the organization of the territory, the distribution of tasks, the sharing of power and the control of resources. Although women are more involved in urban governance elsewhere, their presence in the sphere of urban power in Greater Lomé is still limited. Hence the problem of the low participation of women in the urban governance of Greater Lomé, both in terms of quantity and quality. This study analyzes the presence of women in urban governance of Greater Lomé. To achieve this, the methodology consisted of carrying out a literature review, followed by semi-structured individual interviews. By sorting the objective variables of the target population (ranging from the level of education to monthly income, including marital status and involvement in municipal governance), 384 respondents were selected including actors of sexes, d different ages and professions. The data was collected from June 2022 to November 2023 on 222 women and 162 men spread across the municipalities of Greater Lomé. This population was made up of municipal councilors of both sexes, municipal secretaries, administrative and technical staff as well as resource people. The interview guide included questions about motivations, barriers, financial resources, and school education. The research results show that the current model of urban governance allows the full participation of women, even if their presence remains marginal due to the challenges, they are not able to meet.